Analisis Faktor Ibu Hamil Yang Berhubungan Dengan Kunjungan Antenatal Care Di Puskesmas Rawat Inap Karya Wanita Pekanbaru - Rafika Oktova (STIKES ADVAITA MEDIKA TABANAN, 2019)
One intervention that could reduce the number of deaths and pain is through mother and neonatal of antenatal care. antenatal care that is one of programs such as observation, education and medical treatment for pregnant women in a planned manner. Based on the data from The departement of Health Pekanbaru City (2015), the scope of K1 year 2014 reached 96,1% and coverage of K4 reached 90,42%. The percentage of the scope of K1 anda K4 the lowest is at public health center in patient of Karya Wanita that is about K1 75,5% and K4 66,9%. A lot of factors affect visits antenatal care among others knowledge, education, work, support husband and family income pregnant women. Research purpose to know the pactors pregnant women relating to antenatal care in the public health center in patient of Karya Wanita working areas. Research is analytic design cross sectional. Population research was all the pregant women were 951 people. As the sample 91 taken accidental of sampling. Data analysis by test chi-square (α<0,05). The results of statistical tests chi-square show that there is the correlation between knowledge and family income with visits antenatal care. There was no correlation between education, work and support husband pregnant women with visits antenatal care. Keywords: Knowledge, Education, Work, The Support of Husband, Family Income, Antenatal Care